Migration trends of senior citizens in Poland - Pytel, Sławomir Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Population ageing and migrations are currently the most popular research topics. However, not many researchers combine those two matters, conducting researches only on migrations of elderly people. The following article presents the analysis of senior citizens’ migration trends in Poland. It is preceded by the profile of regional background, which is senior citizens’ migrations in Europe. The study points out places where senior citizens migrate most frequently. Such information may be useful for local authorities to conduct its policy properly.